Enhancing soil ecosystem multifunctionality via carbon input and enzymatic catalysis in cover crops under antibiotic contamination - Ju Wang; Huanhuan Zhang; Jintao Yu; Xuechen Zhang; Mingjun Li; Peizhi Yang; Ziyan Li (Applied Soil Ecology, 2026)

Mechanistic characterization of the discrepancies in enrichment of nitrate between agricultural and urban-industrial rivers in the semi-arid areas of northern China: Insights from multi-element stable isotope analysis - Ang Dong; Yu Liu; Guiqi Liu; Guangzhi Rong; Shuaihao Liu; Mingjun Mo; Haixia Wang; Guoguang Wang (Journal of Hydrology, 2026)

A numerical simulation method for the migration behavior of dispersed fuel particles entrained by molten material during the dispersed fuel melting failure process - Kui Ge; Jiaxin Wu; Jiaxin Zhang; Yuejian Luo; Shihao Wu; Mingjun Zhong; Yapei Zhang; Dahuan Zhu; Wenxi Tian; Hongxing Yu (Annals of Nuclear Energy, 2026)

Decoupling of evapotranspiration from atmospheric demand: mechanistic insights into the local evaporation paradox in arid shrublands via physical and physiological resistance thresholds - Yuquan Qiang; Mingjun Zhang; Yu Zhang; Shengjie Wang; Xianying Xu; Jinchun Zhang; Guiquan Fu; Zhilan Wang; Meilin Sun; Peng Zhao; Shiquan Liu (Journal of Hydrology, 2026)

Structural and operational optimization of cold storage system for enhanced energy efficiency, rapid cold release and economic benefits - Yuan Lv; Zhimei Zuo; Zizhuang Ma; Wang Cheng; Fan Wang; Chuanxiao Cheng; Zheng Ling; Lanlan Jiang; Tao Yu; Mingjun Yang; Lei Yang; Yu Liu; et al. (Journal of Cleaner Production, 2026)

Modeling Hydrate Formation Kinetics and Permeability Evolution: A New Approach Integrating Different Gas-Liquid Contact Modes - Yongqiang Xia; Bingbing Chen; Lanlan Jiang; Lei Yang; Mingjun Yang; Tao Yu; Yongchen Song (Gas Science and Engineering, 2026)

Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

Ah-level small-molecule proton batteries enabled by a cost-effective gradient-porous composite separator - Yu Li; Rui Li; Xinyu Wang; Mengxiao Li; Junjie Wang; Huige Ma; Mengjing Wu; Haiping Yu; Bei Wang; Huijie Wang; Mingjun Hu; Jun Yang (Chemical Engineering Journal, 2026)

Electrostatic interaction induced enhancement of conductive hydrogel for motion detection and targeted identification of ascorbic acid in sweat - Jiarui Liu; Xianghe Zheng; Xinhang Yu; Mingjun Jia; Kai Wei; Liangjiu Bai; Wenxiang Wang; Kun Yin; Lixia Yang; Hou Chen (Analytica Chimica Acta, 2026)

A bimodal phenomenon in lake evolution since the last deglaciation from Qinghai-Tibet Plateau: Multiple hypothesis verification and a new mechanism - Zhansen Zhang; Yu Li; MingJun Gao; Hao Shang; Shiyu Liu; Jiarui Zhao; Tingting Xi; Wanchen Sun (Global and Planetary Change, 2026)

Multilayer-like peptide-lipid nanoparticles enable effective p53 mRNA delivery for tumor suppression in non-small cell lung cancer - Zhe Wang; Weisi Yuan; Meiping Song; Mingjun Zhang; Chunpeng Yang; Weibang Xia; Jiao Chen; Yuhong Zhen; Yu Liu; Hongxu Liu; Yunming Wang; Yinan Zhao; et al. (Chemical Engineering Journal, 2026)

KPF6-assisted two-step hybrid evaporation-solution method for large-area scalable and efficient perovskite solar cells - Tianyu Yu; Mi Zhang; Mingjun Nie; Yunlei Jiang; Shun Zhang; Zixiang Zhou; Lei Shi; Yonggang Yu; Suxia Liang; Yuan Dong (Chemical Engineering Journal, 2026)

Effects of low-molecular-weight organic acids and manganese-modified biochar application sequences on the environmental risk of soil cadmium and arsenic - Yongqiang Yang; Mingjun Li; Yipan Zhao; Liping Li; Yale Wang; Weiqin Xing; Chunhong Xu; Qipo Yang; Yali Wang; Yu Liu (Environmental Geochemistry and Health, 2026)

Efficient inhibition of Microcystis aeruginosa using expanded perlite sustained-release pyrogallic acid: performance studies, mechanistic insights and ecological security assessment - Yuewen Zhang; Mingjun Ma; Yujia Gao; Yu Hong; Xing Xie (Harmful Algae, 2026)

Impacts of the humid climate on the development of two ancient civilizations on the northeastern margin of the Qinghai–Xizang Plateau - Mingjun Gao; Yu Li; Tingting Xi; Jiarui Zhao; Zhansen Zhang; Junjie Duan; Yaxin Xue; Hao Shang; Shiyu Liu (Anthropocene, 2026)

Study on mining pressure law and its influencing factors of deep super-long gangue backfilling working face - Yang Kang; Zhang Qiang; Zou Mingjun; Cui Pengfei; Zong Tingcheng; Zhang Bin; Lv Haonan; Bai Yu; Deng Panbo; Li Jiang (Arabian Journal of Geosciences, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Synergistic effect between biochar and nanoscale zero valent iron effectively mitigated nitrous oxide emissions from a flooded paddy soil - Mingjun Ding; Yu Zhou; Zhe Li; Jian Zhang (Journal of Environmental Chemical Engineering, 2026)

Salicylic acid as a pathway inducer for improved bioremediation of oil-polluted saline-alkali soils by chemotactic S. Stutzeri M3 - Lin Li; Xiaoying Yu; Mingjun Wang; Huaji Sun; Jingyi Zhu; Xuehan Wang; Shuiquan Chen; Shugang Hu (Bioresource Technology, 2026)

The promising effects of bacterial and microalgal inoculants in enhancing tomato growth and improving soil quality - Tongtong Xu; Qixiang Xian; Yunqian Cui; Huali Pei; Wei Liu; Mingjun Chen; Jingling Liu; Hongbo Yu; Nortoji A. Khujamshukurov; Meimei Wu (Biocatalysis and Agricultural Biotechnology, 2026)

Optimal monitoring time of kiwifruit orchard soil moisture content under irrigation using the red-edge indices acquired by UAV-based mutilspectral data - Mingjun Wang; Shidan Zhu; Shouzheng Jiang; Fei Chen; Xiuyun Yu; Lu Zhao; Zongjun Wu; Quanshan Liu; Ningbo Cui; Zhihui Wang; Liwen Xing (Computers and Electronics in Agriculture, 2025)

Disclosing occurrence of typical tire wear particle-derived chemicals in grassland soils from remote pastoral areas, north China - Guoguang Wang; Aoduo Yang; Shuaihao Liu; Mingjun Mo; Haiyue Chen; Guangzhi Rong; Haixia Wang; Yu Liu (Environmental Research, 2025)

Water use strategies of Platycladus orientalis under diverse water management approaches in the western Loess Plateau: Insights from stable isotope analysis - Yu Zhang; Mingjun Zhang; Yuquan Qiang; Rui Lu; Cunwei Che; Shengjie Wang (Plant and Soil, 2025)

Enhanced identification of novel pathogenic variants in hereditary hearing loss through physical phasing with integrated short and long-read sequencing data - Lu Kang; Qian Zhang; Chao Wang; Jia Geng; Xinlei Li; Mingjun Zhong; Sihan Liu; Xuegang Wang; Yu Lu; Jing Cheng; Yongxin Ma; Fengxiao Bu; et al. (Molecular Genetics and Genomics, 2025)

Engineering B₄O₇2−-cross-linked double‑carbon layer separators for mitigating molecular shuttle in rechargeable small-molecule batteries - Xinyu Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Mingsheng Yang; Bei Wang; Haiping Yu; Mengxiao Li; Yuxin Hao; Zhihui Wang; Jingru Liu; Mingjun Hu; et al. (Chemical Engineering Journal, 2025)

Toad’s survivability and soil microbiome alterations impacted via individual abundance - Tian Zhang; Yang Liu; Junde Li; Mingjun Yuan; Chunhan Qiao; Xiao Huang; Xueyao Yang; Bo Gao; Chuan Lou; Yan Yang; Yu Cao (Biologia Futura, 2025)

Weak Fault Feature Extraction for AUV Thrusters with Multi-Input Signals - Dacheng Yu; Feng Yao; Yan Gao; Xing Liu; Mingjun Zhang (Journal of Marine Science and Engineering, 2025)
This paper investigates weak fault feature extraction in AUV thrusters under multi-input signal conditions. Conventional methods often rely on insufficient input signals, leading to a non-monotonic mapping between fault features and fault severity. This, in turn, makes accurate fault severity identification infeasible. To overcome this limitation, this paper increases the number of input signals by utilizing all available measurable signals. To address the problems arising from the expanded signal set, a signal denoising method that combines Feature Mode Decomposition and wavelet denoising is proposed. Furthermore, a signal enhancement technique that integrates energy operators and the Modified Bayes method. Additionally, distinct technical approaches for noise reduction and enhancement are specifically designed for different input signals. Unlike conventional methods that extract features directly from raw input signals, for fault feature extraction and fusion, this study transforms the signals into the time, frequency, and time–frequency domains, extracting diverse fault features across these domains. A sensitivity factor selection method is then employed to identify the sensitive features. These selected features are subsequently fused using Dempster–Shafer evidence theory to construct the final fault feature. Finally, fault severity identification is carried out using the classical grey relational analysis. Pool experiments using the “Beaver II” AUV prototype validate the effectiveness of the proposed method.

LC-MS/MS-based metabolomic of pink Auricularia cornea grown on Lycium barbarum sawdust substrate - Lei Ye; Xuezhen Yang; Zhenzhu Huang; Bo Zhang; Qing Tian; Yu Huang; Wei Tan; Mingjun Feng; Xiaolin Li; Hongbin Xu (Food Chemistry, 2025)

Degradation mechanisms and restoration strategies of Haloxylon ammodendron Forests: Insights from water use and environmental stress - Yuquan Qiang; Mingjun Zhang; Yu Zhang; Xianying Xu; Jinchun Zhang; Guiquan Fu; Peng Zhao; Shengjie Wang (Agricultural and Forest Meteorology, 2025)

Monsoon marginal zone’s dry/wet status and their links with tropical ocean–atmosphere interactions during the Holocene - Yu Li; Zhansen Zhang; Mingjun Gao; Junjie Duan; Yaxin Xue; Hao Shang; Shiyu Liu (Science Bulletin, 2025)

Regulating brønsted/lewis sites of facet-dependent cryptomelane-type MnO2 for simultaneously enhancing performance and N2 selectivity in NOx selective catalytic reduction with NH3 - Changye Mang; Jun Luo; Xiduan Yang; Mingjun Rao; Guipeng Yu; Guanghui Li; Tao Jiang (Chemical Engineering Journal, 2025)

Enhancing hydrological model performance through multi-source open-data utilization in the highly managed, data-scarce basin - Jiayan Zhang; Zhihong Liu; Yu Li; Yanhong Dou; Mingjun Wang; Huicheng Zhou; Bo Xu (Journal of Hydrology, 2025)

Elucidating the co-metabolism mechanism of 4-chlorophenol and 4-chloroaniline degradation by Rhodococcus through genomics and transcriptomics - Yonglin Bo; Yixue Niu; Mingjun Zhu; Yaru Wang; Yu Wang; Yuhua Su; Qiyou Liu; Gang Wang; Yongqiang Wang (Environmental Research, 2025)

Thermoelectric performance in Ag2Se nanocomposites: The role of interstitial Ag and Pb orbital hybridization - Khak Ho Lim; Yuxuan Xia; Lixiang Xu; Mingjun Zhao; Mingquan Li; Ye Cheng; Jiale Mao; Shuang Wang; Lei Chen; Sai Wing Tsang; Pingwei Liu; Qingyue Wang; et al. (Chemical Engineering Journal, 2025)

Global dry-wet patterns under various driving factors and their applications in projecting the future - Junjie Duan; Yu Li; Simin Peng; Yuxin Zhang; Zhansen Zhang; Mingjun Gao; Yaxin Xue; Hao Shang; Shiyu Liu (Quaternary International, 2025)

Selection and validation of reference genes for the normalization of RT-qPCR gene expression data in Rheum tanguticum (Polygonaceae) under various abiotic stresses - Mingjun Yu; Jiarui Jin; Xiaoli Li; Yuping Liu; Xu Su; Marcos A. Caraballo-Ortiz; Penghui Zhang; Qian Yang; Rongju Qu; Zhaxi Cairang; Xuanlin Gao; Yinghui Zheng (Journal of Plant Physiology, 2025)

Contour-constrained branch U-Net for accurate left ventricular segmentation in echocardiography - Mingjun Qu; Jinzhu Yang; Honghe Li; Yiqiu Qi; Qi Yu (Medical & Biological Engineering & Computing, 2025)

Structural evolution and stabilisation mechanism of foam fluids that contain cellulose nanofibres and cellulose nanocrystals: An experimental and theoretical study - Xiaoyang Yu; Huan Li; Ning Kang; Mingjun Xu; Ke Qiu; Ruowen Zong; Shouxiang Lu (Carbohydrate Polymers, 2025)

Exploration of the Formation Mechanism of Underground Brine Based on Hydrodynamic Environment Analysis Using Grain-Size Data of One Drilling Core - Qiao Su; Ying Yu; Mingjun Chen; Tengfei Fu; Wenzhe Lyu; Wenquan Liu (Journal of Marine Science and Engineering, 2024)
The Laizhou Bay area in China harbors a significant amount of Quaternary brine resources, which have been gradually depleted due to intensive long-term exploitation. It is widely accepted that underground Quaternary brine in Laizhou Bay originates from seawater. However, there are disputes regarding the specific form of seawater concentration and the geological processes leading to brine formation. Revealing the genesis of shallow brine in different geological environments is of great scientific significance for resource production and environmental protection. This study analyzed the hydrodynamic conditions of underground brine and adjacent strata based on grain size data, and the possible formation mechanisms of brine layers at different depths were discussed. The mineralization of underground brine is a complex process controlled by various factors, such as specific meteorological and paleogeographic environments, topography, and hydrogeological conditions. On the southern coast of Laizhou Bay, there are three ways in which underground brine layers are formed: residual evaporation from lagoons during the initial regression stage, the hypersaline zone in estuarine lagoons during high-sea-level periods, and brine formation from seawater evaporation on intertidal flats. Turbulent sea–land interactions and the development of river deltas are also necessary conditions for brine mineralization, as they are favorable for replenishing, transporting, and storing underground brine layers.

External ligand-free nickel-catalyzed synthesis of polypyrazines towards stable, high-capacity and low-potential sodium ion storage - Zhihui Wang; Rui Li; Guoqing Zhao; Xiaorong Yan; Xinyu Wang; HaiPing Yu; Yuxin Hao; Yujie Dai; Huige Ma; Mengxiao Li; Hongwei Li; Mingsheng Yang; et al. (Chemical Engineering Journal, 2024)

Spatial heterogeneity of soil moisture caused by drainage and its effects on cadmium variation in rice grain within individual fields - Gaoxiang Huang; Yu Wu; Linxiu Cheng; Dongmei Zhou; Xingxiang Wang; Mingjun Ding; Peng Wang; Yurong Wang (Science of The Total Environment, 2024)

Estimating non-productive water losses in irrigated Platycladus orientalis plantations in semi-arid mountainous: Based on stable isotopes - Yu Zhang; Mingjun Zhang; Yuquan Qiang; Rui Lu; Cunwei Che (Science of The Total Environment, 2024)

Depositional process and sediment dispersal pattern of mass transport complex on a slope with numerous elliptical depressions, northwestern South China Sea - Chao Liang; Chiyang Liu; Xinong Xie; Xiaohang Yu; Lei Huang; Jie Pan; Yunlong He; Hui Chen; Dongmei Tian; Honggang Mi; Mingjun Li; Hui Zhang (Sedimentary Geology, 2024)

A Synthetic Steroid 5α-Androst-3β, 5, 6β-triol Alleviates Radiation-Induced Brain Injury in Mice via Inhibiting GBP5/NF-κB/NLRP3 Signal Axis - Ke Zhong; Kejia Liu; Yu Song; Sitai Chen; Xia Hu; Ruiqi Xue; Xueying Ma; Shaojian Li; Jingwen Yang; Zhenhong Deng; Xiaoqiu Zhu; Mingjun Yuan; et al. (Molecular Neurobiology, 2024)

Comprehensive analysis of histophysiology, transcriptome and metabolome tolerance mechanisms in black porgy (Acanthopagrus schlegelii) under low temperature stress - Yue Wang; Mingjun Shen; Guangping Xu; Han Yu; Chaofeng Jia; Fei Zhu; Qian Meng; Dafeng Xu; Shuran Du; Dianchang Zhang; Zhiwei Zhang (Science of The Total Environment, 2024)

Weak Fault Feature Extraction and Enhancement of Autonomous Underwater Vehicle Thrusters Based on Artificial Rabbits Optimization and Variational Mode Decomposition - Dacheng Yu; Mingjun Zhang; Feng Yao; Jitao Li (Journal of Marine Science and Engineering, 2024)
Variational Mode Decomposition (VMD) has typically been used in weak fault feature extraction in recent years. The problem analyzed in this study is weak fault feature extraction and the enhancement of AUV thrusters based on Artificial Rabbits Optimization (ARO) and VMD. First, we introduce ARO to solve the problem of long-running times when using VMD for weak fault feature extraction. Then, we propose a VMD denoising method based on an improved ARO algorithm to address the issue of deteriorations in the fault feature extraction effect after introducing ARO. In this method, chaotic mapping and Gaussian mutation are used to improve ARO to optimize the parameters of VMD. This leads to a reduced running time and improved fault feature extraction performance. We then perform fault feature enhancement. Due to the unsatisfactory enhancement effect of traditional modified Bayes (MB) methods for weak fault features, we introduce energy operators to transform the fault signals into the energy domain for fault feature enhancement. Finally, we add differential processing to the signal to address the issue of certain fault feature values decreasing after introducing energy operators. In the end, the effectiveness of the proposed methods is verified via pool experiments on a “Beaver II” AUV prototype.

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

Evaluation of the ecohydrological separation of different geomorphological units in a semi-arid area - Yu Zhang; Mingjun Zhang; Yuquan Qiang; Jiaxin Wang; Rong Guo; Deye Qu; Shengjie Wang (Applied Geochemistry, 2024)

Evapotranspiration partitioning based on underlying conductance in a complex tree-grass orchard ecosystem in the humid area of southern China - Ningbo Cui; Shunsheng Zheng; Shouzheng Jiang; Mingjun Wang; Lu Zhao; Ziling He; Yu Feng; Yaosheng Wang; Daozhi Gong; Chunwei Liu; Rangjian Qiu (Agricultural and Forest Meteorology, 2024)

Where and how to cool through blue infrastructure? Large lake groups to ameliorate urban overheating in a typical inland multi-lake megacity - Yatian Cheng; Carlos Bartesaghi-Koc; Yu Tian; Lidu Shen; Mingjun Teng; Huosheng Liu; Zhiyan Xiao; Bin Zhang; Changguang Wu (Sustainable Cities and Society, 2023)

Early–mid Holocene relative sea-level rise in the Yangtze River Delta, China - Yu Cheng; Shiyin Xu; Ding Luo; Bingfei Gao; Mingjun Zhu; Xinqing Zou (Marine Geology, 2023)

Enhanced atmospheric water cycle processes induced by climate warming over the three rivers source region - Zhilan Wang; Meiping Sun; Mingjun Zhang; Lei Zhang; Lailei Gu; Yu Zhang (Atmospheric Research, 2023)

Preemptive QP001, a fast-acting meloxicam formulation, provides analgesia and reduces opioid consumption following abdominal surgery: a randomized controlled trial - Yingyong Zhou; Bin Wang; Kaiming Duan; Zhihong Bai; Xianwen Hu; Mingjun Xu; Xiaohong Li; Yuanli Gao; Jiangang Li; Mengchang Yang; Ying Zhang; Wei Zhang; et al. (Inflammopharmacology, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

Time-scale effects in human-nature interactions, regionally and globally - Yu Li; Mingjun Gao; Zhansen Zhang; Yuxin Zhang; Simin Peng (Journal of Geographical Sciences, 2023)

Octyl gallate targeting the 3C-like protease exhibits highly efficient antiviral activity against swine enteric coronavirus PEDV - Mingjun Su; Baishuang Yin; Xiaoxu Xing; Zijian Li; Jiyu Zhang; Shufeng Feng; Lu Li; Feiyu Zhao; Xu Yang; Shiping Yu; Jun Wang; Yongchen Zhang; et al. (Veterinary Microbiology, 2023)

Degradation-driven bacterial homogenization closely associated with the loss of soil multifunctionality in alpine meadows - Yueju Zhang; Mingjun Ding; Hua Zhang; Nengyu Wang; Ziping Yu; Huan Xu; Peng Huang (Agriculture, Ecosystems & Environment, 2023)

Energy-saving production of high value-added foamed glass ceramic from blast furnace slag and hazardous wastes containing heavy metal ions - Mingjun Li; Feng Zheng; Jiao Wang; Donghua Jia; Xiaodong Mao; Peng Li; Qiang Yuan; Qiang Zhen; Yi Yu (Journal of Cleaner Production, 2023)

Autopolyploidy enhances agronomic traits and active ingredients in ‘Huaibai’, a top-grade medicinal chrysanthemum - Liwei Jiang; Xiaomeng Wang; Zhixian Geng; Yunpeng Wang; Luying Liu; Tianle Wang; Juanjuan Yu; Mingjun Li; Xiting Zhao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

DVPred: a disease-specific prediction tool for variant pathogenicity classification for hearing loss - Fengxiao Bu; Mingjun Zhong; Qinyi Chen; Yumei Wang; Xia Zhao; Qian Zhang; Xiarong Li; Kevin T. Booth; Hela Azaiez; Yu Lu; Jing Cheng; Richard J. H. Smith; et al. (Human Genetics, 2022)

Temporal trends and source apportionment of water pollution in Honghu Lake, China - Shuai Chen; Simeng Wang; Yanxi Yu; Mingjun Dong; Yanqiang Li (Environmental Science and Pollution Research, 2021)

An atlas of CNV maps in cattle, goat and sheep - Yongzhen Huang; Yunjia Li; Xihong Wang; Jiantao Yu; Yudong Cai; Zhuqing Zheng; Ran Li; Shunjin Zhang; Ningbo Chen; Hojjat Asadollahpour Nanaei; Quratulain Hanif; Qiuming Chen; et al. (Science China Life Sciences, 2021)

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication - Ran Li; Peng Yang; Ming Li; Wenwen Fang; Xiangpeng Yue; Hojjat Asadollahpour Nanaei; Shangquan Gan; Duo Du; Yudong Cai; Xuelei Dai; Qimeng Yang; Chunna Cao; et al. (Science China Life Sciences, 2021)

Over-Expressed FEZF1 Predicts a Poor Prognosis in Glioma and Promotes Glioma Cell Malignant Biological Properties by Regulating Akt-ERK Pathway - Mingjun Yu; Shijia Yu; Yixue Xue; Hai Yu; Duo Chen; Xiangtai Wei; Yunhui Liu (Journal of Molecular Neuroscience, 2018)

Displacement and Dissolution Characteristics of CO $$_{2}$$ 2 /Brine System in Unconsolidated Porous Media - Lanlan Jiang; Minghao Yu; Ying Teng; Mingjun Yang; Yu Liu; Weizhong Li; Yongchen Song (Transport in Porous Media, 2018)

Planar block adjustment and orthorectification of Chinese spaceborne SAR YG-5 imagery based on RPC - Taoyang Wang; Guo Zhang; Deren Li; Ruishan Zhao; Mingjun Deng; Tong Zhu; Lei Yu (International Journal of Remote Sensing, 2018)

The Effect of Divalent Metal Ions and Recycle Ratio of UASB Reactor on the Formation of Anammox Granules and Its Treatment Performance - Jinxiang Fu; Mingjun Zhou; Jie Yun; Yang Su; Pengfei Yu; Ming Sun; Xinqi Ji (Water, Air, & Soil Pollution, 2017)

Characteristics and possible formation mechanisms of severe storms in the outer rainbands of Typhoon Mujiga (1522) - Bingyun Wang; Ming Wei; Wei Hua; Yongli Zhang; Xiaohang Wen; Jiafeng Zheng; Nan Li; Han Li; Yu Wu; Jie Zhu; Mingjun Zhang (Journal of Meteorological Research, 2017)

Microsatellite-centromere mapping in Japanese scallop (Patinopecten yessoensis) through half-tetrad analysis in gynogenetic diploid families - Qi Li; Mingjun Qi; Hongtao Nie; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2016)

Overexpression of NPC1L1 in the livers of transgenic Bama miniature pigs accelerates lipid peroxidation - Chongli Xu; Yu Liu; Yuchen Gong; Xinping Duan; Xiaochun Tang; Mingjun Zhang; Daxin Pang; Liqing Yu; Hong Wei; Hongsheng Ouyang (Genes & Genomics, 2015)

In-situ observation for formation and dissociation of carbon dioxide hydrate in porous media by magnetic resonance imaging - ChuanXiao Cheng; JiaFei Zhao; YongChen Song; ZiHao Zhu; WeiGuo Liu; Yi Zhang; MingJun Yang; XiChong Yu (Science China Earth Sciences, 2013)

SNIP1: a new activator of HSE signaling pathway - Qiang Li; Jian An; Xianghua Liu; Mingjun Zhang; Yichen Ling; Chenji Wang; Jing Zhao; Long Yu (Molecular and Cellular Biochemistry, 2012)

The conditioned medium from a stable human GDF3-expressing CHO cell line, induces the differentiation of PC12 cells - Qiang Li; Xianghua Liu; Yanhua Wu; Jian An; Saiyin Hexige; Yichen Ling; Mingjun Zhang; Xianmei Yang; Long Yu (Molecular and Cellular Biochemistry, 2012)

Cyclophilin A promotes human hepatocellular carcinoma cell metastasis via regulation of MMP3 and MMP9 - Mingjun Zhang; Chun Dai; Hengrui Zhu; Shuai Chen; Yanhua Wu; Qiang Li; Xianzhuo Zeng; Wenzhang Wang; Jie Zuo; Mei Zhou; Zongjun Xia; Guoqing Ji; et al. (Molecular and Cellular Biochemistry, 2011)

Characterization of a novel human HMBOX1 splicing variant lacking the homeodomain and with attenuated transcription repressor activity - Mingjun Zhang; Shuai Chen; Qiang Li; Yichen Ling; Jie Zhang; Long Yu (Molecular Biology Reports, 2010)

Characterization of a novel human CDK5 splicing variant that inhibits Wnt/β-catenin signaling - Qiang Li; Xianghua Liu; Mingjun Zhang; Guangming Ye; Qian Qiao; Yichen Ling; Yanhua Wu; Yuanyuan Zhang; Long Yu (Molecular Biology Reports, 2010)